Bereavement through drugs and alcohol. Issue 2 (3rd May 2016) - Lawton, Helen; Gilbert, James; Turnbull, Fiona
Abstract : Bereavement through a friend or relative's drug or alcohol use is a devastating, challenging and often isolating experience. Despite many different circumstances, those bereaved through drugs or alcohol share many experiences. In this article Helen Lawton and James Gilbert share their stories of bereavement, and Fiona Turnbull's commentary draws out some common elements found in drug and alcohol related bereavement.